2018
DOI: 10.1021/acs.nanolett.8b02738
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Switchable Monostable Actuatoric Polymer-Based Nanovalve Arrays with a Long-Term Stability

Abstract: Here we present a novel electrically switchable nanovalve array based on an intrinsic conductive polymer that has the capabilities to change its volume depending on its redox state. The polymer is created by anodic deposition of a sodium dodecylbenzenesulfonate (DBS)-doped polypyrrole (PPy). Optimization of the DBS-doped PPy layers revealed an actuatoric performance of up to 10% out of plane volume change. More interestingly, the electrochemical characterization revealed an actuatoric monostable polymer that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Therefore, it can be used as an actuator. This kind of material can be miniaturized for component design, making it a microelectronic mechanical system device that is widely used in microrobots, microvalves, biomedical electronic devices and other fields [ 247 , 248 , 249 , 250 , 251 , 252 ].…”
Section: Application Of Ppy Nanomaterialsmentioning
confidence: 99%
“…Therefore, it can be used as an actuator. This kind of material can be miniaturized for component design, making it a microelectronic mechanical system device that is widely used in microrobots, microvalves, biomedical electronic devices and other fields [ 247 , 248 , 249 , 250 , 251 , 252 ].…”
Section: Application Of Ppy Nanomaterialsmentioning
confidence: 99%
“…For example, nanoporous aluminum oxide substrates with polypyrrole as electrochemically volume changing material have been explored to control the flow of fluorescently labelled biotin and bovine serum albumin [84,85] . The latter with drug delivery applications in mind [85] .…”
Section: Separation Applicationsmentioning
confidence: 99%
“…Volume changes of CPs have been mainly used in actuators and drug delivery devices, [16,17] while their application in smart filters is barely explored. [18][19][20] Prönnecke et al [20] demonstrated Polypyrrole-dodecylbenzenesulfonate (PPy-DBS)/Al 2 O 3 -based nanoporous filters where the flow rate of biotin could be decreased by 90% when PPy-DBS was electrochemically addressed and the porosity of the filter decreased. In another example, Tan et al demonstrated active PPy-DBS/PVDF ultrafiltration membranes.…”
Section: Introductionmentioning
confidence: 99%